The Spanish Language as a Cultural and Touristic Resource for the Chinese Market to Develop Quality Education - García-Henche, Blanca; Yang, Ming (Frontiers in Psychology, 2022)
Since 1952, Spanish has been included as a degree in Foreign Language Studies in the higher education system in China. The number of Spanish students has gradually increased and, until March 2020, with the 6 Universities recently approved by the Chinese Ministry of Education, there are 102 Chinese universities that teach Spanish as a university degree. In 2017, the Ministry of Education of the People's Republic published the Curriculum Plan in Higher Secondary Schools, which incorporated the teaching of Spanish as a teaching option along with other languages such as English, Japanese, Russian, German and French. In the following year, during the Chinese President's State visit in Spain and due to his meeting with his Spanish counterpart, between the Royal Spanish Academy (abbreviated as RAE for its Spanish name) and Shanghai International Studies University (SISU), a cooperation agreement was signed, under which a Joint Research Centre between RAE and SISU was established. This work aims to publicize the situation of Spanish teaching in China, showing how language can become a cultural and language tourism resource for our country, Spain. An empirical study of student profiles will be carried out at one of the most prestigious universities in reference to Spanish teaching in China, Shanghai International Studies University (SISU). The data were obtained through primary sources employing a survey sent to Chinese students studying their bachelor’s degree of Spanish Philology, obtaining a sample of 159 students. The results revealed information on studies carried out, also reviewing the most popular universities among Chinese students in Spain, their stay period and the destination image that the students have. The data will serve to show the opportunities for Spain as a destination for language tourism for the Chinese market. One of the implications of this work would be that it helps to explain how Spain can design a product for a niche market that demands Spain as a destination for language and cultural tourism.